1996
DOI: 10.1002/masy.19961100103
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with interlaboratory GPC experiments

Abstract: Based on some round robin experiments organized in the last years by a DIN working group and by the IUPAC working party IV.2.2, the paper discusses measures for getting a better interlaboratory reproducibility of GPC results. The most important points are: ‐ selecting columns according to their separation selectivity and range ‐ avoiding artifacts in the distribution curves, caused by gaps in the pore volume distribution ‐ avoiding adsorption and memory effects ‐ calibration: using calibration standards of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 2 publications
2
28
0
Order By: Relevance
“…Subsequently, the obtained chromatogram is broadened according to Equation (1) and (2). Finally, the chromatogram is retranslated into an MMD by applying the respective calibration for the EMG parameters used in the broadening process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the obtained chromatogram is broadened according to Equation (1) and (2). Finally, the chromatogram is retranslated into an MMD by applying the respective calibration for the EMG parameters used in the broadening process.…”
Section: Resultsmentioning
confidence: 99%
“…Deviations from expected values are frequently ascribed to sidereactions and/or non-ideal polymerization conditions. Several effects such as the correct selection of the baseline [1] and the correct calibration process [2,3] have been proven to be important parameters in SEC and could decisively increase the performance of an analysis if chosen wisely. However, it should be stressed that band broadening (BB), which is a rather complex and indeed non-avoidable instrumental feature of SEC, prevents the precise measurement of molar masses and leads to measured characteristic values that deviate from ideal ones.…”
Section: Introductionmentioning
confidence: 99%
“…1. M n is however the least reproducible and least accurate molecular weight quantity that can be determined using SEC ( [26] (http://old.iupac.org/projects/posters01/berek01.pdf), [27]). Accuracy of 15% is the best that can be expected and the deviation observed in Fig.…”
Section: Importance Of the Injection Concentrationmentioning
confidence: 99%
“…This method is applicable to isorefractive polymers or copolymers. Alternative methods to determine M n are also of high interest since M n appears to be the quantity determined in SEC with the lowest accuracy ( [26] (http://old.iupac.org/projects/ posters01/berek01.pdf), [27]). The Goldwasser method has however attracted little attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the difference between the apparent and true molar masses is insignificant for PEMA (lower than 2%); it is lower than the experimental error coming from the SEC analysis itself, evaluated at roughly 5 to 10% for M w and 15 to 20% for M n . [29] It should be noted that a difference in tacticity could lead to an additional 20% error in the case of PEMA. [30] In our study, however, the PMMA standards and the investigated PEMA samples had similar syndiotactic contents.…”
Section: Experimental Part Materialsmentioning
confidence: 99%